Health-related quality of life in patients with liver cirrhosis following adjunctive nurse-based care versus standard medical care: a pragmatic, multicentre, randomised controlled study - Anncarin Svanberg; Maria Hjorth; Daniel Sjöberg; Elenor Kaminsky; Fredrik Rorsman; Riccardo Lo Martire (BMJ Open Gastroenterology)
Objectives Patients have difficulties in understanding how to manage their liver cirrhosis. This highlights a need for support in comprehending health-related information, which remains largely lacking within liver cirrhosis care. Involvement of registered nurses (RNs) in outpatient liver cirrhosis care has potential to improve quality of care and reduce patient mortality. However, the benefits of nursing care on patients’ health-related quality of life (HRQoL) are scarcely studied. This study compared HRQoL in patients receiving either standard medical outpatient care or adjunctive, nurse-led care. The risk of malnutrition, decompensation events and mortality were also compared between the two study groups.Methods This was a pragmatic, multicentre, randomised trial, which enrolled 167 patients with liver cirrhosis. The primary outcome measure, HRQoL, was assessed using the RAND-36 questionnaire. The physical component summary (PCS) and the mental component summary (MCS) scores of RAND-36 were compared, using linear mixed-effects models for repeated measures, at 12 and 24 months.Results 83 patients received standard medical care, and 84 patients received adjunctive, nurse-led care for 24 months. Due to unforeseen circumstances, the final study population of 167 participants was less than the intended 500. Group comparisons were non-significant of the PCS and MCS scores (−1.1, p=0.53 and −0.7, p=0.67, respectively), malnutrition (p=0.62) and decompensation events (p=0.46), after 24 months. However, mortality was three times higher in the control group compared with the intervention group (12 vs 4, p=0.04) after 24 months.Conclusions In this study, adjunctive nurse-led care was not superior to standard medical outpatient care regarding HRQoL, risk of developing malnutrition or decompensation. However, RN involvement contributed to early identification of decompensation and reduced mortality.Trial registration number NCT02957253.